2016
DOI: 10.1093/ckj/sfw116
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome in biopsy-proven acute interstitial nephritis treated with steroids

Abstract: Background: There are no prospective randomized controlled trials describing the outcome of acute interstitial nephritis (AIN) treated with steroids, and retrospective studies are limited. Methods: We identified adult patients with a diagnosis of AIN without glomerular pathology over a 14-year period. Treated patients all received oral prednisolone and three also recieved IV methylprednisolone. Data were collected retrospectively on estimated glomerular filtration rate (eGFR), change in eGFR from time of biops… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
59
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(68 citation statements)
references
References 31 publications
5
59
1
3
Order By: Relevance
“…Four of these studies did not find a significant difference in change of serum creatinine levels between the corticosteroid and the non‐corticosteroid groups, while two studies reported significant differences . The two other studies that did not perform statistical analyses concluded that corticosteroids improved renal function . These studies had small sample sizes and true differences between groups were not assessed with statistical measures.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Four of these studies did not find a significant difference in change of serum creatinine levels between the corticosteroid and the non‐corticosteroid groups, while two studies reported significant differences . The two other studies that did not perform statistical analyses concluded that corticosteroids improved renal function . These studies had small sample sizes and true differences between groups were not assessed with statistical measures.…”
Section: Resultsmentioning
confidence: 98%
“…Four of the eight studies ascribed no ADR to corticosteroids, without further details provided . One study reported that 4.7% of patients developed diabetes; however, it was unclear if this ADR applied only to patients with DI‐AIN or AIN from other causes …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations